Realizing high thermoelectricity in polycrystalline tin sulfide via manipulating fermi surface anisotropy and phonon dispersion. (August 2020) - Wu, H.; Peng, K.; Zhang, B.; Gong, X.N.; Feng, Z.Z.; Zhang, X.M.; Xi, M.; Yan, X.M.; Zhang, Y.S.; Wang, G.Y.; Lu, X.; Zhou, X.Y.
Abstract: Tin sulfide (SnS) with an analogous structure to SnSe has attracted increasing attentions owing to its low cost, earth abundance, and environmental compatibility. In this work, the thermoelectric properties of polycrystalline SnS1- x Se x (0 ≤ x ≤ 0.5) are systematically investigated. With the assistance of the theoretical calculations and experimental results, the intrinsic characteristic of the markedly diminished lattice thermal conductivity with increasing Se alloying content is due to the decreased phonon vibration frequency associated with the reduced phonon group velocity and the strengthened phonon scattering. In addition, compared with SnS, the more localized Sn_5s 2 lone pair electrons in SnS0.5 Se0.5 are propitious to strengthen the anisotropy of Fermi surface and lattice anharmonicity, leading to high quality factor ( B ). Finally, a highest zT value (~1.1) at 820 K is obtained for Na0.02 Sn0.98 S0.5 Se0.5 by optimizing the carrier concentration through Na doping. These results contribute to a comprehensive understanding of the modification of phonon dispersion and band structure of SnS-SnSe solid solutions and indicate their high thermoelectric performance in SnS-based materials. Graphical abstract: These changes in the intrinsic characteristics that the disappearance of frequency gap, enhanced Grüneisen parameters, and reduced the phonon group velocities via Se alloying, further together with point defects, lead to a significant decrease in the lattice thermal conductivity. Image 1 Highlights: The intrinsic characteristic of reduced lattice thermal conductivity via Se alloying, compared with SnS, is attributed to weakened bonds and enlarged mass contrast, and the disappearance of frequency gap and the large Grüneisen parameters verified by the theoretical calculations and experimental results. The favorable transport coefficients and quality factor ( B ) are obtained in SnS0.5 Se0.5, referred to SnS, which is due to the fact that the more localized Sn_5s 2 lone pairs electrons result in the strengthening of Fermi surface anisotropy and lattice anharmonicity. A peak figure of merit ( zT ) value of ~1.1 at 820 K is obtained for Na0.02 Sn0.98 S0.5 Se0.5, which is one of the best thermoelectric sulfides in terms of the peak zT.